Scrutinizing Discord as an Advanced Platform to Support Students’ Listening Proficiency (A Theoretical Perspective) - Nabil Nabil Aldebarant; Yulis Setyowati; Hreesang Satria Bagaskara; Surya Priyambudi (EL2J (English Language and Literature Journal), 2023)
Discord serves as a widely used social media platform among millennials around the globe and it enables seamless communication during online gaming sessions. A few studies on the use of Discord still are limited. Therefore, this research paper seeks to propose the utilization of discord as a means in a listening class. The article offers empirical evidence supporting the considerable in what way discord will be affordable in listening class. Initially, the paper reviews previous studies that have explored the most recent social media used by teenagers that is Discord, Telegram, and TikTok. Then, it gives some practical ways how to use Discord in listening class. Subsequently, this paper elucidates the ways in which Discord can boaster learners effectively to comfortable and enjoyable listening comprehending exercises for university students. Finally, a summary is provided at the conclusion of the paper, offering an overview of its main points.